THE CORRELATION BETWEEN PAST TENSE MASTERY AND WRITING SKILL IN PERSONAL RECOUNT TEXT - Dewi Agustini; Yuyun Hendrety; Farnia Sari (Didascein : Journal of English Education, 2021)
Past tense mastery supports the students’ writing skill in personal recount text. Considering the importance of past tense in the text construction, the investigation concerned on the correlation between past tense mastery and writing skill in personal recount text of the tenth grade students of SMA Arinda Palembang. The objective of this study was to find out whether there was a significant correlation between past tense mastery and writing skill in personal recount text of the tenth-grade students of SMA Arinda Palembang. The sample of this study was 62 students taken from X1 and X2 of SMA Arinda Palembang by using purposive sampling technique. The method used in this study was a quantitative method with a correlational research. The data collected were writing test and past tense mastery test. The result of this study showed that there was no a significant correlation between students’ past tense mastery and writing skill in personal recount text in low category. It was proved by correlation coefficient between students’ past tense mastery and writing skill was 0.633 (rxy ) at the significance level 0.062 was higher than 0.05. On the basis of the finding, the writers concluded that there is no a significant correlation between students’ past tense mastery and writing skill. It means that when students have minimum level of past tense mastery, it did not mean that they also get poor achievement in writing.Past tense mastery supports the students’ writing skill in personal recount text. Considering the importance of past tense in the text construction, the investigation concerned on the correlation between past tense mastery and writing skill in personal recount text of the tenth grade students of SMA Arinda Palembang. The objective of this study was to find out whether there was a significant correlation between past tense mastery and writing skill in personal recount text of the tenth-grade students of SMA Arinda Palembang. The sample of this study was 62 students taken from X1 and X2 of SMA Arinda Palembang by using purposive sampling technique. The method used in this study was a quantitative method with a correlational research. The data collected were writing test and past tense mastery test. The result of this study showed that there was no a significant correlation between students’ past tense mastery and writing skill in personal recount text in low category. It was proved by correlation coefficient between students’ past tense mastery and writing skill was 0.633 (rxy ) at the significance level 0.062 was higher than 0.05. On the basis of the finding, the writers concluded that there is no a significant correlation between students’ past tense mastery and writing skill. It means that when students have minimum level of past tense mastery, it did not mean that they also get poor achievement in writing.Keywords:  past tense, writing skill, personal recount text